Minnesota Stormwater Research and Technology Transfer Program – A Comprehensive Approach to Collaborative Research. (30th December 2021) - Bilotta, John P.; Peterson, Jeffrey M.
Abstract: The University of Minnesota Water Resources Center (UMN WRC) in collaboration with the Minnesota Stormwater Research Council (MSRC) has developed a robust program to advance urban stormwater management and policy through the completion of research. Through this unique collaboration, stormwater professionals and researchers across Minnesota are engaged in multi‐sector research to prevent, minimize, and mitigate urban stormwater impacts by studying existing and innovative structural and non‐structural practices, policies, and management techniques. The center and the council have evolved a comprehensive approach by: Obtaining diversified funding resulting in an annual average $1M budget. Coordinating and building partnerships at local, regional, state, and federal levels to leverage stormwater research resources. Using the council to engage with stormwater researchers, professionals, policymakers, and stakeholders.  Identifying strategic priorities through assessments of needed research (i.e., the Minnesota Stormwater Research Roadmap). Providing a process for prioritizing, soliciting, submitting, approving, and implementing stormwater‐related research proposals. The program also invests in technology transfer seeking the effective and efficient dissemination of research results to those who can best benefit from it. The council is an organization of stormwater professionals, practitioners, managers, engineers, researchers, and others established in 2016 to work with the center to facilitate relevant, applied research and support education and technology transfer. This paper summarizes the efforts of the program, the future outlook, and highlights the collaboration and the connection of the University and the center to agencies, local units of government, and private engineering consulting businesses, who all were integral to the success of the program.